Social services for the elderly: a multivariate perspective study - Vega-Hernández, María-Concepción; Román-Gallego, Jesús-Ángel; Pérez-Delgado, María-Luisa; Torres-García, Ana-Victoria (Frontiers in Psychology, 2023)
Introduction: Today's society is aware that healthy aging favors quality of life in the future, even more so as life expectancy increases in populations such as Europe. As in countries such as Japan, it is necessary for institutions to provide social services to support the elderly, with the aim of achieving an optimal quality of life for these people. The aim of this study is to analyze the different types of social services and activities that certain institutions provide to the elderly in order to find areas for improvement or to propose relationships between them that will benefit both users and institutions.Methods: Official data from Junta de Castilla y León (Spain) on social services for the elderly in the 9 provinces of the autonomous community of Castilla y León from 2007 to 2021 were analysed using multivariate statistical techniques.Results: Throughout the period under analysis, there is an association between the number of places in public and private non-profit residential centres for the elderly and the number of places in daycare centres or the number of students in the Inter-University Experience Programme. The variables associated with the telecare programme are related to the number of people under guardianship. On the other hand, three well-differentiated clusters of provinces of Castilla y León were observed.Discussion: Our findings have implications for the quality of life of the elderly, as the differences in social services in the areas analysed have a direct impact on the health of the elderly.